The Profile of Road Traffic Injury-Related Fracture Patient in the Emergency Department of H. Damanhuri Barabai General Hospital - Firdaus, Muhammad Nanda; Pratista, Muhammad Bagas; Rahman, Ansari; Putera, Husna Dharma; Noor, Zairin ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2025)
Background: Road traffic injuries (RTIs) are a major cause of fractures, posing significant challenges for healthcare systems especially in rural areas. Based on data from to Traffic Corps of the Indonesian National Police published by the Ministry of Transportation, the number of traffic accidents in Indonesia reached 103,645 cases in 2021. Understanding the profile of RTI-related fracture patients is crucial to improve emergency care and guide preventive strategies. This study aims to identify the profile of the RTI-related fracture patient in the emergency department of H. Damanhuri Barabai General Hospital. Methods: This study was retrospective observational. We analysed the medical records of RTI-related fracture patients in Emergency Department of H. Damanhuri Barabai General Hospital during March – July 2023. We observed gender, age, mode of injury, type of fracture and bone involved. Results: There were 91 RTI-related fracture patients from 146 orthopaedic patients recorded. Male had a higher incidence (74%). The highest incidence was observed in 41 – 60 ages group (32%) and 21 - 40 ages group (31%). The most common mode of injury was double traffic injuries (65%) involving motorcycle vs motorcycle (41%). The primary type of fracture was identified as closed fracture (63%). The   bone most involved was tibia (27%). Conclusions: Fractures are common among males during their productive years as a result of traffic injuries. This study provides insights that advance understanding to the prevalence of RTI-related fractures. Additional research is required to develop further overview of RTI-related fractures.